PERILAKU PERSONAL HYGIENE TERHADAP KEJADIAN SKABIES DI PESANTREN JABALNUR WILAYAH KERJA PUSKESMAS DEWANTARA KABUPATEN ACEH UTARA - Nisa Ul Husna; Asriwati Asriwati; Endang Maryanti (Jurnal Kesehatan dan Fisioterapi, 2023)
Complaints of scabies are caused by a lack of personal hygiene in humans. This study aims to analyze the effect of personal hygiene behavior on the incidence of scabies in the Jabalnur Islamic Boarding School in the working area of the Dewantara Public Health Center, North Aceh Regency.  This research is an analytic survey with a cross sectional study design which was conducted at the Jabalnur Islamic Boarding School in the working area of the Dewantara Public Health Center, North Aceh Regency, from August to September 2022. The sample consisted of 89 people using purposive sampling technique. Data were analyzed using Chi Square test and Logistic Regression.  Based on the results of the study, it was found that there was an effect of hand and nail hygiene (p=0.004), clothing cleanliness (p=0.000), towels cleanliness (p=0.000), bed cleanliness (p=0.035) and clean water facilities (p=0.000) ) to the incidence of scabies in the Jabalnur Islamic Boarding School in the working area of the Dewantara Health Center, North Aceh Regency. The personal hygiene variable that most dominantly influences the incidence of scabies in the Jabalnur Islamic Boarding School in the working area of the Dewantara Health Center, North Aceh Regency is the towel hygiene behavior variable.  The conclusion of the study is that there is an effect of hand and nail hygiene, clothing cleanliness, towel cleanliness, bed cleanliness and clean water facilities on the incidence of scabies in the Jabalnur Islamic Boarding School working area of the Dewantara Health Center, North Aceh Regency.  Based on the conclusions in this study, it is suggested that the results of this study can be used as evidence based on preventing the incidence of scabies by paying attention to aspects of personal hygiene. Keywords: Personal Hygiene, Scabies Incidence